A conceptual framework of consumers’ intention to purchase halal food among Gen Z in Malaysia / Norraeffa Md Taib, Shahreena Daud and Zarinah Abu Yazid - Md Taib, Norraeffa; Daud, Shahreena; Abu Yazid, Zarinah (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
The purpose of this paper is to develop a conceptual framework that provides insights and aids in understanding the factors that influence consumers’ intention to purchase halal food among Gen Z in Malaysia. This concept paper explains the relationship between attitude, subjective norms, and perceived behavioural control towards purchase intention on halal food among Gen Z in Malaysia. Based on an extensive literature review, this paper proposes a conceptual framework for understanding the relationship and relevant insights on its development. The study uses a descriptive research approach in order to gain fruitful insights as well as to explain the relationship between attitude, subjective norms, and perceived behavioural control that influence purchase intention on halal food among Gen Z in Malaysia. A structured questionnaire will be given to the respondents in assessing their purchase intention on halal food. The results of this study discovered the importance of consumers’ purchase intention of halal food products. It is hoped that this paper would serve as a reference to Malaysian Statutory bodies and halal food industry specifically on the current purchase intention of halal food among Malaysia’s Gen Z.